Sosialisasi dan Edukasi Bahaya Narkoba bagi Siswa-Siswi SMPN 4 Tewah, Kabupaten Gunung Mas, Provinsi Kalimantan Tengah - Pereiz, Zimon; C, Chuchita; Oksal, Efriyana; Telaumbanua, Mesra Ratna Sari; Sabatini, Felly; J, Julia; Solla, Angelia; Catur Prasetyo, Debby; Hutabalian, Gracyela; A, Anjelika; H, Heja; Florensia, Ornella Arnia; Devianti, Gusnia; Apriyanti, Mauliya; Prayoga, Andika; Tundan, Arisumi Ir L; Dandy, Jonathan; A, Abdullah (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
A community service activity entitled "Socialization and Education on the Dangers of Drugs for Students of SMPN 4 Tewah, Gunung Mas Regency, Central Kalimantan Province" was conducted as an early prevention effort against drug abuse among students. This outreach program aimed to provide a comprehensive understanding of the negative impacts of drugs from a health, social, educational, and legal perspective. The method used was interactive delivery of material through presentations, discussions, and question-and-answer sessions, enabling students to participate more actively and relate the knowledge gained to their daily lives. The results of the program demonstrated that it was well-run and effective. This was evidenced by a significant increase in student understanding based on pre- and post-test evaluations, with an understanding score of 94.8%. These findings demonstrate that the outreach and education on the dangers of drugs can positively contribute to raising student awareness of the importance of staying away from drugs. Thus, this activity serves not only as a learning tool but also as a strategic step in developing a healthy, productive, and integrated young generation.